النظام القانوني لصندوق التقاعد في الجزائر - نجم الدين جوامع; أحسن بن حشيش (My University, 2017)
Summary: Through our study of the legal system of the National Pension Fund in Algeria, we have found that the efforts made by the various actors in the field of social security, as well as the various reforms, especially the legislation, have made this body independent of the rest of the social security funds. "The legislator has devoted a set of laws to determine its legal nature, which is financially and administratively independent and morally personalized and has also defined its administrative organization in line with its mandated tasks. However, the Fund continued to suffer from a number of problems in terms of its financing, particularly as a result of the large number of pensioners, as well as the transitional phase of Algeria's economic reforms, which resulted in the closure of public institutions, which resulted in a reduction in the number of participants and the amount of contributions. ............................. الملخص : من خلال دراستنا لموضوع النظام القانوني للصندوق الوطني للتقاعد في الجزائر اتضح لنا بأن المجهودات التي بذلت من طرف مختلف الأطراف الفاعلة في مجال الضمان الاجتماعي وكذا الإصلاحات المختلفة وخاصة التشريعية منها استطاعت أن تجعل من هذه الهيئة جهازا مستقلا عن باقي صناديق الضمان الاجتماعي ، وقد افرد له المشرع مجموعة من القوانين تحدد طبيعته القانونية وهو صندوق مستقل ماليا وإداريا ويتمتع بالشخصية المعنوية وحدد له أيضا تنظيمه الإداري وفق ما يتماشى مع المهام المنوطة به ، إلا أن هذا الصندوق ظل يعاني من عدة مشاكل من ناحية تمويله خاصة نتيجة كثرة المحالين على التقاعد وكذا المرحلة الانتقالية التي مرت بها الجزائر بعد الإصلاحات الاقتصادية المتبعة والتي نتج عنها غلق المؤسسات العمومية مما أدى إلى تقليص عدد المشتركين ومبلغ الاشتراك دون أن ننسى كذلك أن انتزاع الصبغة الإدارية منه وإخضاعه لنظام قانوني خاص زاد من حدة المشاكل في هذا المجال . ................................. Résumé : Par notre étude du système juridique de la Caisse nationale des pensions en Algérie, nous avons constaté que les efforts déployés par les différents acteurs dans le domaine de la sécurité sociale, ainsi que les diverses réformes, notamment législatives, Le CST est indépendant des autres caisses de sécurité sociale. "Le législateur a consacré un ensemble de lois pour déterminer sa nature juridique, qui est financièrement et administrativement indépendante et moralement personnalisée et a également défini son organisation administrative en ligne avec ses tâches mandatées. Toutefois, le Fonds a continué à rencontrer un certain nombre de problèmes en termes de financement, notamment du fait du grand nombre de retraités, ainsi que de la phase transitoire des réformes économiques en Algérie qui ont entraîné la fermeture d’institutions publiques, qui a entraîné une réduction du nombre de participants et du montant des contributions.